Functional physical training improves fitness and cognitive development in 4~5 years old children - Hao, Lei; Fan, Yongzhao; Zhang, Xiaojuan; Rong, Xiangjiang; Sun, Youping; Liu, Kun (Frontiers in Psychology, 2023)
Background Development of physical and cognitive function is very critical in 4~5 years children. It has been addressed in this research if the 18 weeks of specific functional training with or without cognitive training can be effective on improving fitness and cognitive development in 4~5 years preschool children. Methods A total of 126 preschool children in the 4~5 age range were selected as participants and randomly assigned to one of four groups: the control group (C), the functional physical training group (P), the cognitive training group (CT), and the functional physical training combined with cognitive training group (PCT). Results The results revealed significant pre/post differences in body height and weight among all four groups of children. Furthermore, there was no significant difference in physical fitness between the C group and the CT group after the intervention. However, the children in the P group and the PCT group showed significant improvements in three indicators including standing long jump, continuous jump, and 10-meter shuttle running. Additionally, the children in P group, CT group, and the PCT group demonstrated significant improvement in simple reaction time, attention, and spatial memory. No significant cognitive improvement was found in C group. Conclusion Functional physical training with or without cognitive intervention can promote both physical fitness and cognitive development in children aged 4~5 years. Cognitive training alone can significantly improve cognitive function but not physical. Therefore, functional physical training can be used alone to improve the physical and cognitive abilities for aged 4~5 years old children.